MATHEMATICAL MODELS OF INVENTORY MANAGEMENT OF MANY TYPES OF GOODS - Raximova Umida Ziyadullayevna (Galaxy International Interdisciplinary Research Journal, 2023)
This work is devoted to the optimization of inventory management. It explores the problems of effective implementation of multi-holding decision-making and provides mathematical models of the problems.